A high dynamic weak spread spectrum signal acquisition strategy based on the transfer model. Issue 1 (1st December 2022) - Yang, Fan; Meng, Zhijun; Wang, Guangming; Guo, Xiye; Yan, Enqi; Zhang, Yufeng
Abstract: To solve the problem of low Earth orbit (Leo) satellite constellation link spread spectrum signal acquisition in the high dynamic weak environment, this paper proposes a acquisition strategy based on transfer model. In this paper, we analyze the dynamic characteristics of link signal. An improved method of parallel code phase search acquisition based on transfer model acquisition strategy is introduced, the improvement of the proposed acquisition strategy to the traditional acquisition algorithm is illustrated through theoretical analysis. Simulation results verify the superiority of the acquisition strategy based on the transfer model for high dynamic weak signal acquisition.